2020
DOI: 10.3390/s20051285
|View full text |Cite
|
Sign up to set email alerts
|

LiDAR-Based System and Optical VHR Data for Building Detection and Mapping

Abstract: The aim of this paper is to highlight how the employment of Light Detection and Ranging (LiDAR) technique can enhance greatly the performance and reliability of many monitoring systems applied to the Earth Observation (EO) and Environmental Monitoring. A short presentation of LiDAR systems, underlying their peculiarities, is first given. References to some review papers are highlighted, as they can be regarded as useful guidelines for researchers interested in using LiDARs. Two case studies are then presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Recently, studies in literature have moved towards data integration in order to improve the accuracy of urban LULC classification [15,16]. Data integration refers to the integration of information from various sources or sensors, such as the integration of LiDAR and optical data, for instance [17][18][19]. Nevertheless, even these techniques used in LULC classification present some issues since they are extremely affected by the environmental changes, like destruction of essential wetlands, uncontrolled urban development, haphazard, loss of prime agricultural lands, deteriorating environmental quality, and also by other factors, like cloud cover and regional fog errors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, studies in literature have moved towards data integration in order to improve the accuracy of urban LULC classification [15,16]. Data integration refers to the integration of information from various sources or sensors, such as the integration of LiDAR and optical data, for instance [17][18][19]. Nevertheless, even these techniques used in LULC classification present some issues since they are extremely affected by the environmental changes, like destruction of essential wetlands, uncontrolled urban development, haphazard, loss of prime agricultural lands, deteriorating environmental quality, and also by other factors, like cloud cover and regional fog errors.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, even these techniques used in LULC classification present some issues since they are extremely affected by the environmental changes, like destruction of essential wetlands, uncontrolled urban development, haphazard, loss of prime agricultural lands, deteriorating environmental quality, and also by other factors, like cloud cover and regional fog errors. Moreover, traditional remote-sensing imagery processing offers some other concerns: the noise associated with the image, the orientation of features in the images and the maintenance of a large volume of data [19,20]. Several methodologies have been developed by the researchers to address those issues faced in LULC classification.…”
Section: Introductionmentioning
confidence: 99%
“…Using these models, the angles of inclinations were estimated. In [5], two case studies based on the use of 2D and 3D LiDARs showed that LiDAR allows the extraction of accurate building features and accomplishes in monitoring and analysis of relevant areas. The combination of TLS and photogrammetry for structural monitoring are shown in [6].…”
Section: Introductionmentioning
confidence: 99%
“…This approach allows the scanning of large objects on the one hand, but on the other it is flexible and easily reprogrammable. 3D scanners can also be used to scan larger areas, such as robotic production cells or even entire buildings [30,31]. The limitations of the sensor's design must be taken into account, as the use of the IR detector requires appropriate environmental conditions to eliminate interference.…”
Section: Introductionmentioning
confidence: 99%